Six of crows - Bardugo, Leigh (Square Fish, an imprint of Macmillan Publishing Group, LLC [2015], 2015)
Ketterdam: a bustling hub of international trade where anything can be had for the right price--and no one knows that better than criminal prodigy Kaz Brekker. Kaz is offered a chance at a deadly heist that could make him rich beyond his wildest dreams. But he can't pull it off alone: A convict with a thirst for revenge, a sharpshooter who can't walk away from a wager, a runaway with a privileged past, a spy known as the Wraith, a Heartrender using her magic to survive the slums, and a thief with a gift for unlikely escapes. Six dangerous outcasts. One impossible heist. Kaz's crew is the only thing that might stand between the world and destruction--if they don't kill each other first. -- Provided by publisher